2021
DOI: 10.1002/cmdc.202100676
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Lung Cancer Activities of 1,2,3‐Triazole Curcumin Derivatives via Regulation of the MAPK/NF‐κB/STAT3 Signaling Pathways

Abstract: In this study, a series of curcumin derivatives containing 1,2,3triazole were designed and synthesized, and their inhibitory activities against the proliferation of lung cancer cells were studied. Compound 5 k (3,4-dichlorobenzyltriazole methyl curcumin) had the best activity against A549 cells, with a halfmaximal inhibitory concentration (IC 50 ) of 2.27 μM, which was approximately 10 times higher than that of the lead curcumin and higher than that of gefitinib (IC 50 = 8.64 μM). Western blotting revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…MAPK inhibitors can inhibit NF-κB phosphorylation and reduce TNF-stimulated IL-6 gene expression [ 51 ]. Triazole derivatives have been shown to play an anti-inflammatory role via inhibiting NF-κB activation and MAPK phosphorylation [ 52 , 53 ], but its effects in AD need to be further explored. In our present study, we found that W112 may potentially inhibit MAPKs/NF-κB signal pathways to reverse Aβ-induced AD-like lesions both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK inhibitors can inhibit NF-κB phosphorylation and reduce TNF-stimulated IL-6 gene expression [ 51 ]. Triazole derivatives have been shown to play an anti-inflammatory role via inhibiting NF-κB activation and MAPK phosphorylation [ 52 , 53 ], but its effects in AD need to be further explored. In our present study, we found that W112 may potentially inhibit MAPKs/NF-κB signal pathways to reverse Aβ-induced AD-like lesions both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, researchers have not fully elucidated the mechanisms of MS13 against NSCLC, so further analysis is needed. With a triazole ring, the analog compound 5k regulates multiple signaling pathways, including MAPK activation and STAT3 and NF-κB inhibition, to reduce lung tumor development [ 162 ]. Although PI3K-AKT pathways play a significant role in tumor growth, invasion, migration, and apoptosis, 5k does not influence PI3K-AKT pathways [ 162 ].…”
Section: The Impact Of Cur Analogs On Nsclcmentioning
confidence: 99%
“…p38 MAPK and STAT3 signalling are activated in most of cancer cells and participate in cancer cell proliferation and metastases 21,22 . Suppression of p38 MAPK and STAT3 activation was associated with reduced lung cancer growth in vitro and in animal models 23,24 . However, the role and downstream signalling pathways of SIRPα in the progression of lung cancer are not well studied so far.…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 Suppression of p38 MAPK and STAT3 activation was associated with reduced lung cancer growth in vitro and in animal models. 23 , 24 However, the role and downstream signalling pathways of SIRPα in the progression of lung cancer are not well studied so far. We in this study, for the first time, investigated the role of SIRPα in SIRPα knock‐out (KO) mice and found that lack of SIRPα significantly reduced lung cancer cell growth in mice, in association with improved MPs and neutrophils (NPs) phagocytosis and reduced IL‐6 expression in tumour tissues.…”
Section: Introductionmentioning
confidence: 99%